(untitled) (Journal of Contemporary Philology, 2019)
The paper investigates the phenomenon of inverted subjects in Macedonian as an instance of a word order governed by pragmatics. It presents an analysis of seman-tic, syntactic and discourse interface that produces postverbal subjects with unac-cusative verbs at sentence and discourse level. Using evidence from a sample of collected examples from different written sources (literary, academic and popular texts) the authors show that subject-verb inversion occurs in presentative and even-tive constructions which introduce a new referent or a new event into the discourse. The results of the analysis confirm the main hypothesis that inversion results from the interplay of pragmatic principles at a sentence and discourse level. The marked information structure triggers inversion if it fulfills a cohesive function in the dis-course. In literary texts, inversion serves an additional pragmatic function as it as-signs a topical status to the subject referent and creates an eye-witness effect in presenting the described situation.